Atomistic tensile deformation mechanisms in a CrCoNi medium-entropy alloy with gradient nano-grained structure at cryogenic temperature - Tao, Yuhao; Cheng, Wenqiang; Wang, Wei (Frontiers in Materials, 2023)
Large-scale molecular dynamics (MD) simulations have been utilized to reveal the atomistic deformation mechanisms of a CrCoNi medium-entropy alloy (MEA) with gradient nano-grained (GNG) structure in the present study. Strong strain hardening was observed in the GNG structure at the elasto-plastic transition stage, which could be attributed to the Masing hardening. After yielding, obvious partitioning of tensile strain was detected in the GNG structure, which indicates the existence of hetero-deformation induced (HDI) hardening effect and could account for the higher flow stress of the GNG structure than that calculated by the rule of mixture from its homogenous nano-grained (NG) structured counterparts. Moreover, partitioning of stacking fault factor (corresponding to the partitioning of tensile strain), which demonstrates the intensity of dislocation behaviors, was also observed in the GNG structure. The differences of factors for each grain size area were found to be smaller in the GNG structure than those of its homogeneous NG structured counterparts, which indicates the influence of forward stress and back stress on dislocation motion near the zone boundary between the hard zone with smaller grains and the soft zone with larger grains, further verifying the presence of HDI hardening in the GNG structure.